Depression and the Risk of All-Cause and Cardiovascular Mortality in Patients With Chronic Obstructive Pulmonary Disease: A Study From NHANES 2005–2018 - Hui Wei; Fachao Shi; Qin We; Bin Wang; Guoqin Qiu; Caoyang Fang (Canadian Respiratory Journal)
Conclusion: In COPD patients, depression is associated with higher risks of both cardiovascular and overall mortality. However, further validation of this finding is needed in large-scale prospective studies with sufficient follow-up time.